The Impacts of Covid-19 Pandemy in Term of Technology Literacy Usage on Students Learning Experience - Mezia Kemala Sari; Efri Yoni (Institut Teknologi Sepuluh Nopember, 2021)
This study aims at investigating the positive impact of the Covid-19 pandemic which has changed the learning process from offline to online. The research focuses on the use of the internet as a means of technological literacy which is the reference for research on student learning experiences. This study uses a comparative descriptive method by comparing internet usage before and during the pandemic related to the learning process. A structural questionnaire link using google form was sent to students through WhatsApp. A total of 36 students provided complete information regarding the survey. The simple percentage distribution was used to assess the learning status of the study participants. The results showed that there was a significant increase in the use of technology and internet literacy where downloading, uploading, attending workshops, webinars, and online competitions increased by using many online learning applications. The positive impact that can be seen is the increase in digital skills of students and lecturers as shown by their creativity and willingness to be more active, which of course supports online learning